Lateral Compartment Contact Pressures Do Not Increase After Lateral Extra-articular Tenodesis and Subsequent Subtotal Meniscectomy. Issue 6 (25th June 2019) - Shimakawa, Tomoyuki; Burkhart, Timothy A.; Dunning, Cynthia E.; Degen, Ryan M.; Getgood, Alan M.
Background: Modified Lemaire lateral extra-articular tenodesis (LET) has been proposed as a method of addressing persistent anterolateral rotatory laxity after anterior cruciate ligament (ACL) reconstruction (ACLR). However, concerns remain regarding the potential for increasing lateral compartment contact pressures. Purpose: To investigate changes in tibiofemoral joint contact pressures after isolated ACLR and combined ACLR plus LET with varying states of a lateral meniscal injury. Study Design: Controlled laboratory study. Methods: Eight fresh-frozen cadaveric knee specimens (mean age, 60.0 ± 3.4 years) were utilized for this study, with specimens potted and loaded on a materials testing machine. A pressure sensor was inserted into the lateral compartment of the tibiofemoral joint, and specimens were loaded at 0°, 30°, 60°, and 90° of flexion in the following states: (1) baseline (ACL- and anterolateral ligament–deficient), (2) ACLR, (3) ACLR with LET, (4) partial meniscectomy (removal of 50% of the posterior third of the lateral meniscus), (5) subtotal meniscectomy (removal of 100% of the posterior third of the lateral meniscus), and (6) LET release (LETR). Mean contact pressure, peak pressure, and center of pressure were analyzed using 1-way repeated-measures analysis of variance. Results: Across all flexion angles, there was no statistically significant increase in the mean contact pressure or peak pressure after ACLR plus LET with and without lateral meniscectomy compared with isolated ACLR. There was a significant reduction in the mean contact pressure, from baseline, after subtotal meniscectomy (69.72% ± 19.27% baseline; P = .04) and LETR (65.81% ± 13.40% baseline; P = .003) at 0° and after the addition of LET to ACLR at 30° (61.20% ± 23.08% baseline; P = .031). The center of pressure was observed to be more anterior after partial (0°, 30°) and subtotal (0°, 60°) meniscectomy and LETR (0°, 30°, 60°). Conclusion: Under the loading conditions of this study, LET did not significantly alter lateral compartment contact pressures when performed in conjunction with ACLR in the setting of an intact or posterior horn–deficient lateral meniscus. Clinical Relevance: This study should provide surgeons with the confidence that it is safe to perform LET in this manner in conjunction with ACLR without altering lateral compartment pressures, regardless of the status of the lateral meniscus.